2019
DOI: 10.1097/md.0000000000014744
|View full text |Cite
|
Sign up to set email alerts
|

Nucleostemin expression in breast cancer is a marker of more aggressive phenotype and unfavorable patients’ outcome

Abstract: Cancer stem cells (CSCs) are postulated to play significant role in the pathogenesis, progression as well as drug resistance of breast cancer. Nucleostemin (NS) is thought to be a key molecule for stemness, and the clinical impact of NS immunoreactivity in breast cancer can indicate its actual role and future therapeutic potentials.The current study is an observational study with an attempt to evaluate the correlation between NS expression (protein and gene expression levels) and different clinicopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A number of studies have also described the association of GNL3 gene overexpression with tumor progression and poor survival in cancer of the prostate [ 38 ], stomach [ 39 ], colon [ 40 ], breast [ 41 , 42 ], and lung [ 43 ]. For three other identified genes ( QSOX2 , SSPO , and SYS1 ), we have described potential involvement in PCa for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also described the association of GNL3 gene overexpression with tumor progression and poor survival in cancer of the prostate [ 38 ], stomach [ 39 ], colon [ 40 ], breast [ 41 , 42 ], and lung [ 43 ]. For three other identified genes ( QSOX2 , SSPO , and SYS1 ), we have described potential involvement in PCa for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced expression of GNL3 gene, encoding for nucleostemin, is particularly interesting in the context of OC tumors since this protein has been found to have a role in the migration ability and in the epithelial-mesenchymal transition of OC cells [ 30 ]. A dysregulated expression of GNL3 has been observed in several cancer cells and it was found to be associated with forced cell growth and survival, increased propensity to metastasize as well as with enhanced resistance to therapies, relapse and poor prognosis [ 25 , 26 , 27 , 28 , 29 ]. Interestingly, OTX015 and IR combination showed an enhanced effect in reducing the expression of GNL3 protein, this having a potential benefit in counteracting radioresistance mechanisms and so improving the therapeutic efficacy against OC tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the information about the anticancer effects of different BETi agents, mainly JQ1 drug, in OC [ 20 , 21 , 22 , 23 ], it is useful to investigate their molecular mechanisms and their precise targeted factors both as monotherapies and combined with conventional treatments. Our recent observations have linked OTX015 antitumor activity to a marked downregulation of GNL3 gene [ 11 ], coding for the G nucleolar 3 protein (often indicated as nucleostemin) that is implied in growth, survival, genome stability and stemness capacities of various cancer cell types [ 24 ], this being also related with cancer resistance to conventional treatments [ 24 , 25 , 26 , 27 , 28 ]. Currently, only few studies have correlated the aberrant expression of GNL3 gene with OC tumorigenesis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EMT was found to be associated with Ki67 PI and basal-like tumors [57]. Further, the expression of nucleostemin was found to be higher in less differentiated, more advanced stage, larger, and lymphnode-positive tumors, as well as in more aggressive molecular subtypes (HER2+ and TN) when evaluated in 51 patient archival specimens from the UAE, although none of these associations reached statistical significance [58]. A study from Oman observed a statistically significant relationship between high elastosis and ER positivity (p = 0.015) and HER2-status (p = 0.045) in 80 female patients who were not treated with neoadjuvant therapy from 2009 to 2019, suggesting that elastosis may be used as a surrogate marker for ER positivity and HER2 negativity in BC [59].…”
Section: Other Biomarkersmentioning
confidence: 94%